Long-term reactivity transient analysis in an extended loss of all AC power at the Koeberg nuclear plant - Foster, Neil (Department of Electrical Engineering, 2022)
This study investigates, through neutronics and thermodynamic modelling of the Koeberg Nuclear Station, a 900 MW pressurized water reactor (PWR), whether extended loss of all AC power (ELAP) scenarios will result in an uncontrolled return to criticality. The purpose is to determine whether recriticality can be avoided without performing plant modifications, or significantly adjusting the existing procedures to depressurize the primary system. The concern is that many currently proposed solutions introduce the risk of further complications, such as a loss of reactor coolant accident (LOCA). The Fukushima Daiichi accident in 2011 was caused by a tsunami that resulted in an extended loss of all AC power at the power station, causing a major nuclear accident, highlighting the importance of introducing measures to deal with ELAP scenarios over and above the short-term AC power loss scenarios previously catered for. The immediate concern in an ELAP is to ensure sufficient removal of heat from the primary system. This is achieved by providing adequate secondary side feed-water and steam-evacuation capability from the steam generators, and maintaining an adequate volume of borated water in the primary system, to prevent overheating of the reactor core. However, in the ELAP scenario, a long-term reactivity concern develops as additional reactivity is introduced into the core by the cooling of the moderator (during the course of recovery actions) which is compounded by the decay of neutron poisons in the core. The xenon isotope 135Xe is a significant neutron poison which accumulates in the fuel of an operating nuclear reactor. Its presence in the fuel of a recently-tripped reactor initially helps to maintain subcriticality, but this eventually decays away. This depletion starts at about 8 hours after a reactor trip, gradually adding more reactivity to the core. If borated water cannot be injected into the primary system to compensate for this, the reactor could return to criticality in an uncontrolled manner. Although this would be self-limiting (due to re-heating of the moderator and fuel), and not catastrophic in itself, the undesired generation of additional nuclear power in the reactor would, by consuming already limited supplies of cooling water, decrease the time available for recovery before the fuel in the reactor core overheats and melts. Utilities have made proposals to maintain sub-criticality in an ELAP scenario, which do not require AC power. They involve introducing boron into the primary system. They are often costly, and some proposals require the operator to open the primary system relief valves, introducing an additional risk of a failure of the relief valves to close, leading to a loss of coolant accident, and a core melt. The primary aim of the study was to determine, in an ELAP scenario, whether it is necessary to provide additional boron injection (over and above the existing accumulator inventory) to maintain the reactor sub-criticality. This was achieved using neutronics and thermodynamic modelling of Koeberg Nuclear Power Station. Another area of focus was to confirm that the existing cooldown strategies to mitigate ELAP events, are sufficient to maintain sub-criticality. After modelling and assessing the ELAP scenario over four different stages of the fuel cycle, it was concluded that, with best estimate assumptions, the selected reactivity acceptance criteria were met. However, with assumptions that envelope the majority of fuel cycle variances and code uncertainty (i.e. greater than 97.5% of cases), meeting the acceptance criteria for the latter part of the fuel cycle could not be demonstrated. Some potential solutions to ensure long-term sub-criticality are proposed.